2012
DOI: 10.1021/ja308104k
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Trimerization of Bis-silylated Diazomethane

Abstract: (Me(3)Si)(2)CNN isomerizes upon addition of traces of [Me(3)Si](+) ions to give (Me(3)Si)(2)NNC, which then undergoes an unusual trimerization reaction to give exclusively 4-diazenyl-3-hydrazinylpyrazole. As catalyst the isonitrilium ion, [(Me(3)Si)(2)NNC(SiMe(3))](+), was identified and fully characterized. Experiments and computations indicate a three-step reaction including isomerization of diazomethane, a C-C or N-C coupling, and a formal cycloaddition reaction. The kinetics and thermodynamics are discusse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

7
3

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 110 publications
1
25
0
Order By: Relevance
“…Therefore, cyanidation greatly increases the thermodynamic stability of all cyanidoborates relatively to the perfluorinated [BF 4 ]ion, or B(CN) 3 represents a very strong Lewis acid, which is much stronger than BF 3 . Furthermore, the CIA values supports this finding as they increase considerably along BF 3 Si-X-LA] (X = halogen or CN -) in the reactions of Me 3 Si-X with Lewis acids has been described previously, [52][53][54][55][56][57][58] and silylium ions have been isolated and used in catalysis. [59][60][61][62][63] Notably, the catalytic cycles in Scheme 7 are proposals based on the assumption that Lewis acids in the presence of a strong donor (such as Me 3 SiCN) form adducts (e.g., LA-NC-SiMe 3 ) that diminish their acidity compared with those of the free acids.…”
Section: Thermodynamic Considerations -Catalysissupporting
confidence: 59%
“…Therefore, cyanidation greatly increases the thermodynamic stability of all cyanidoborates relatively to the perfluorinated [BF 4 ]ion, or B(CN) 3 represents a very strong Lewis acid, which is much stronger than BF 3 . Furthermore, the CIA values supports this finding as they increase considerably along BF 3 Si-X-LA] (X = halogen or CN -) in the reactions of Me 3 Si-X with Lewis acids has been described previously, [52][53][54][55][56][57][58] and silylium ions have been isolated and used in catalysis. [59][60][61][62][63] Notably, the catalytic cycles in Scheme 7 are proposals based on the assumption that Lewis acids in the presence of a strong donor (such as Me 3 SiCN) form adducts (e.g., LA-NC-SiMe 3 ) that diminish their acidity compared with those of the free acids.…”
Section: Thermodynamic Considerations -Catalysissupporting
confidence: 59%
“…Startingf rom these parent compounds, derivativesc an be generated by successive substitution of protons with monovalentg roups. Sinces ilyliumi ons, in particular, the [Me 3 Si] + , are often referredt oa sl arge protons, [11][12][13][14][15][16] they have also been used to synthesize onium ions to stabilize them kinetically. Sinces ilyliumi ons, in particular, the [Me 3 Si] + , are often referredt oa sl arge protons, [11][12][13][14][15][16] they have also been used to synthesize onium ions to stabilize them kinetically.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, recrystallization from Et 2 O yielded crystals of [Et 2 OSiMe 3 ][B(C 6 F 5 ) 4 ] · m ‐xylol. Although the compound [Et 2 OSiMe 3 ][B(C 6 F 5 ) 4 ] was already reported, its synthesis usually involved Me 3 Si + transfer reagents . It can be concluded that the intermediate, formed in the reaction of 1 with [Ag( m ‐xylol) 3 ][B(C 6 F 5 ) 4 ], is a strong silylating agent.…”
Section: Resultsmentioning
confidence: 99%